The association of physical activity with perceived fatigability among community-dwelling older adults aged ≥60 years in regional China - Bin Yang; Qing Ye; Xiaojing Deng; Zhiyong Wang; Caihong Hu; Yeping Bian; Jian Xu; Fei Xu (Preventive Medicine Reports, 2025)
Objectives: This study aimed to investigate the association of physical activity with perceived fatigability among community-dwelling older adults in regional China. Methods: Totally, 5484 community-dwelling residents aged 60+ years were randomly chosen from Nanjing municipality of China in this cross-sectional study in 2023. The outcome variable, perceived physical and mental fatigability, was assessed with the validated Chinese version of Pittsburgh Fatigability Scale. The independent variable, physical activity, was measured with the Chinese version of International Physical Activity Questionnaire. Mixed-effect logistic regression models were employed to compute odds ratios (ORs) and 95 % confidence intervals (95 %CIs) for examining associations of physical activity with both physical and mental fatigability. Results: Among overall participants, the prevalence of physical and mental fatigability was 59.0 % (95CI = 57.7, 63.0) and 51.1 % (95 %CI = 49.8, 52.4), respectively. After adjustment for potential confounders, participants with sufficient physical activity were less likely to perceive either physical (OR = 0.66; 95 %CI = 0.55, 0.81) or mental (OR = 0.68; 95 %CI = 0.56, 0.83) fatigability compared to their counterparts with insufficient physical activity. Moreover, such negative associations of physical activity with physical and mental fatigability were observed for participants stratified by age/gender, with an exemption for the relationship between physical activity and physical fatigability in participants aged 80+ years. Conclusions: Physical activity was negatively associated with either physical or mental fatigability for overall or age−/gender-specific community-dwelling residents aged 60+ years in regional China. This study has important implications for building healthy-aging societies, since it is possible to prevent or mitigate both physical and mental fatigability for older adults through population-level physical activity promotion.